PENGARUH PENGGUNAAN FLASHCARDS TERHADAP KEMAMPUAN PENGENALAN EMOSI ANAK USIA 4-6 TAHUN - Kelisha, Innara; Romansza, Hana Kameliana; Sanjaya, Alvin; Susanto, Lorentius Rossi Dwi; Pangestu, Gold Stefen; Risnawaty, Widya (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
This study aims to examine the effectiveness of flashcard media in improving emotion recognition skills in children aged 4-6 years. The research background highlights the importance of early emotion recognition, as preschool-aged children begin to display basic emotions, but their skills in recognizing and managing emotions remain limited. The study employed a quantitative method with a pretest-posttest design, involving five students from TK Bhakti YKKP Kemanggisan. Children were given an initial test to assess their emotion recognition abilities, followed by an intervention using the “Know Your Emotions” flashcards featuring eight basic emotions. After the intervention, a post-test was conducted to evaluate changes in emotion recognition skills. The results showed a significant improvement in children’s ability to recognize emotions after using flashcards. As an engaging and simple visual medium, flashcards proved effective in helping children identify and understand various emotions more specifically and interactively. Flashcards can be applied both at school and at home, thus supporting the optimal development of children’s emotional intelligence. ABSTRAKPenelitian ini bertujuan menguji efektivitas media flashcards dalam meningkatkan kemampuan pengenalan emosi pada anak usia 4-6 tahun. Latar belakang penelitian menyoroti pentingnya pengenalan emosi sejak dini, karena anak usia prasekolah mulai mampu menunjukkan berbagai emosi dasar, namun keterampilan mereka dalam mengenali dan mengelola emosi masih terbatas. Metode yang digunakan adalah kuantitatif dengan desain pretest-posttest, melibatkan lima murid TK Bhakti YKKP Kemanggisan. Anak-anak diberikan tes awal untuk mengukur kemampuan pengenalan emosi, kemudian dilakukan intervensi menggunakan flashcard “Know Your Emotions” yang menampilkan delapan emosi dasar. Setelah intervensi, dilakukan tes akhir untuk menilai perubahan kemampuan pengenalan emosi. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam kemampuan anak mengenali emosi setelah penggunaan flashcard. Flashcard sebagai media visual yang menarik dan sederhana terbukti efektif membantu anak mengenali dan memahami berbagai emosi secara lebih spesifik dan interaktif. Penggunaan flashcard dapat diterapkan baik di sekolah maupun di rumah, sehingga mendukung perkembangan kecerdasan emosional anak secara optimal.